"Efectividad del programa educativo en el nivel de conocimientos sobre métodos anticonceptivos en adolescentes. El Porvenir - Muñoz Matencio, Cynthia Mishel (2015)
This research study, experimental pre guy, was held in the Educational Institution: José María Arguedas, during the months of December 2014 - January 2015, in order to determine the effectiveness of the educational program at the level of knowledge about contraception in adolescents. The sample consisted of 32 adolescents who met the inclusion criteria. The instrument used for data collection: Standard Survey Methods Contraceptive Knowledge, being the information obtained, processed and analyzed by statistical test "t student" for related samples; the results are presented in graphs and crosstab. After the analysis has led to the following conclusions: Before implementing the education program contraception, 50.0 percent of teens got a low level of knowledge, 46.9 percent average knowledge level of 3.1 percent and a high level of knowledge; after application of the educational program on contraception, 78.1 percent have a medium level of knowledge and 21.9 percent a higher level of knowledge. Finally, I determine that the educational program was effective presenting significant to improve the level of knowledge about contraception in adolescents who participated in the study change.